STRATEGY TO PREVENT MASSIVE RECRUITMENT OF THE TERRORIST ORGANIZATIONS IN INDONESIA DURING THE COVID-19 PANDEMIC - Gia Ayu Fita; Stanislaus Riyanta (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
During the Covid-19 pandemic, the movement of the terrorist groups or the radical groups, which should have been "dead" or remained silent during the pandemic, still takes place. Such a situation has compelled the researcher to conduct a study since the aim of the study is to explore the potential threats and objectives of terrorism in Indonesia during the pandemic. In conducting the study, terrorist recruitment theory and strategy theory are implemented along with the hierarchy of human needs to describe the reasons behind the active terrorist recruitment during the pandemic. The relevant data for the study are gathered through the implementation of interviews for collecting the primary data and library study for gathering the secondary data. After the data have been gathered, the data are analyzed using qualitative data analysis so that the case of active terrorist recruitment during the pandemic can be better described. Then, the results of the study conclude that massive recruitment is a new threat to efforts to prevent and eradicate terrorism because radical groups can mobilize many resources, especially human resources, to achieve their agenda and goals without being directly involved in executions in the field and the most accessible means to use in this massive recruitment effort is mass media because social media has anonymity, a broad spectrum, and low cost as a means of mass communication. Therefore, to stem the influence of radical groups on social media, security forces need to become social media as the main battlefield with several strategies such as increasing cyber patrols, blocking access to websites of radical groups, developing a critical understanding of cyberspace content or information, and empowering counter-opinions